Thymic Stromal Lymphopoietin Isoforms, Inflammatory Disorders, and Cancer - Varricchi, Gilda; Pecoraro, Antonio; Marone, Giancarlo; Criscuolo, Gjada; Spadaro, Giuseppe; Genovese, Arturo; Marone, Gianni (Frontiers in Immunology, 2018)
Thymic Stromal Lymphopoietin (TSLP) is a pleiotropic cytokine originally isolated from a murine thymic stromal cell line. TSLP exerts its biological effects by binding to a high affinity heteromeric complex composed of TSLPR chain and IL-7R. TSLP is primarily expressed by activated lung and intestinal epithelial cells, keratinocytes, and fibroblasts. However, dendritic cells, mast cells and presumably other immune cells can also produce TSLP. Different groups of investigators have demonstrated the existence of two variants for TSLP in human tissues: the main isoform expressed in steady state is the short form (sf TSLP), which plays a homeostatic role, whereas the long form (lfTSLP) is upregulated in inflammatory conditions. In addition, there is evidence that in pathological conditions TSLP can be cleaved by several endogenous proteases. Several cellular targets for TSLP have been identified, including immune (dendritic cells, ILC2, T and B cells, NKT and Treg cells, eosinophils, neutrophils, basophils, monocytes, mast cells, and macrophages) and non-immune cells (platelets and sensory neurons). TSLP has been originally implicated in a variety of allergic diseases (e.g., atopic dermatitis, bronchial asthma, eosinophilic esophagitis). Emerging evidence indicates that TSLP is also involved in chronic inflammatory (i.e., COPD, celiac disease) and autoimmune (e.g., psoriasis, rheumatoid arthritis) disorders and several cancers. These emerging observations greatly widen the role of TSLP in different human diseases. Most of these studies have not used tools to analyze the expression of the two TSLP isoforms. The broad pathophysiologic profile of TSLP has motivated therapeutic targeting of this cytokine. Tezepelumab is a first-in-class human monoclonal antibody (1) that binds to TSLP inhibiting its interaction with TSLP receptor complex. Tezepelumab given as an add-on-therapy to patients with severe uncontrolled asthma has shown safety and efficacy. Several clinical trials are evaluating the safety and the efficacy of tezepelumab in different inflammatory disorders. mAbs used to neutralize TSLP should not interact or hamper the homeostatic effects of sf TSLP.